Apolipoprotein A-I in Labeo rohita: Cloning and functional characterisation reveal its broad spectrum antimicrobial property, and indicate significant role during ectoparasitic infection. (August 2016) - Mohapatra, Amruta; Karan, Sweta; Kar, Banya; Garg, L.C.; Dixit, A.; Sahoo, P.K.
Abstract: Apolipoprotein A-I (ApoA-I) is the most abundant and multifunctional high-density lipoprotein (HDL) having a major role in lipid transport and potent antimicrobial activity against a wide range of microbes. In this study, a complete CDS of 771 bp of Labeo rohita (rohu) ApoA-I ( LrApoA-I ) encoding a protein of 256 amino acids was amplified, cloned and sequenced. Tissue specific transcription analysis of LrApoA-I revealed its expression in a wide range of tissues, with a very high level of expression in liver and spleen. Ontogenic study of LrApoA-I expression showed presence of transcripts in milt and 3 h post-fertilization onwards in the larvae. The expression kinetics of LrApoA-I was studied upon infection with three different types of pathogens to elucidate its functional significance. Its expression was found to be up-regulated in the anterior kidney of L. rohita post-infection with Aeromonas hydrophila . Similarly following poly I:C (poly inosinic:cytidylic) stimulation, the transcript levels increased in both the anterior kidney and liver tissues. Significant up-regulation of LrApoA-I expression was observed in skin, mucous, liver and anterior kidney of the fish challenged with the ectoparasite Argulus siamensis . Immunomodulatory effect of recombinant LrApoA-I (rApoA-I) produced in Escherichia coli was demonstrated against A. hydrophila challenge in vivo . L. rohita administered with rApoA-I at a dose of 100 μg exhibited significantly higher protection (∼55%) upon challenge with A. hydrophila 12 h post-administration of the protein, in comparison to that observed in control group, along with higher level of expression of immune-related genes. The heightened expression of ApoA-I observed post-infection reflected its involvement in immune responses against a wide range of infections including bacterial, viral as well as parasitic pathogens. Our results also suggest the possibility of using rApoA-I as an immunostimulant, particularly rendering protection against A. hydrophila . Highlights: Apolipoprotein A-I of Labeo rohita was cloned and sequenced. LrApoA-I expression was noticed in wide range of tissues except eye and brain. LrApoA-I was expressed in milt and 3 h post-fertilization during ontogeny. A remarkably high level of expression was noticed during Argulus siamensis infection. rApoA-I was found to be antimicrobial and immunomodulatory in nature.